The Dynamics of Opportunity in America 2016
DOI: 10.1007/978-3-319-25991-8_9
|View full text |Cite
|
Sign up to set email alerts
|

Quality and Equality in American Education: Systemic Problems, Systemic Solutions

Abstract: After briefl y reviewing the unequal opportunities outside schools that contribute to the disparities in educational achievement, attainment, and various indicators of adult success, this chapter zeroes in on addressing inequities within K-12 education. We argue that disparities within the educational system are the product of institutional structures and cultures that both disenfranchise certain groups of students and depress quality overall. Systemic causes require systemic solutions, and we envision a three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 45 publications
2
28
0
Order By: Relevance
“…Despite the paucity of research on self-generated linking selfquestions, based on findings regarding the beneficial effects of implementing externally generated self-questions into scientific text reading tasks (e.g., Greene et al, 2010;Kostons and Van Der Werf, 2015), we predicted that the students in the two experimental groups (Within-Text and Extra-Text) would outperform the control group on all scientific literacy measures after training. Regarding the two experimental groups' comparison, in line with previous research on the importance of prior knowledge for reading comprehension of scientific texts (e.g., Gunn, 2008;Kaberman and Dori, 2009;Berkeley et al, 2011;Moseley et al, 2016;Joseph and Ross, 2018), the Extra-Text (Elaboration) group was expected to achieve higher scientific literacy results than the Within-Text (Bridging) group.…”
Section: The Current Studysupporting
confidence: 57%
See 1 more Smart Citation
“…Despite the paucity of research on self-generated linking selfquestions, based on findings regarding the beneficial effects of implementing externally generated self-questions into scientific text reading tasks (e.g., Greene et al, 2010;Kostons and Van Der Werf, 2015), we predicted that the students in the two experimental groups (Within-Text and Extra-Text) would outperform the control group on all scientific literacy measures after training. Regarding the two experimental groups' comparison, in line with previous research on the importance of prior knowledge for reading comprehension of scientific texts (e.g., Gunn, 2008;Kaberman and Dori, 2009;Berkeley et al, 2011;Moseley et al, 2016;Joseph and Ross, 2018), the Extra-Text (Elaboration) group was expected to achieve higher scientific literacy results than the Within-Text (Bridging) group.…”
Section: The Current Studysupporting
confidence: 57%
“…Previous studies have found that when students connect their prior knowledge to science text reading, their reading comprehension achievements improve (Kendeou and Van Den Broek, 2007;Moos and Azevedo, 2008;Kaberman and Dori, 2009;Ozuru et al, 2009;Moseley et al, 2016;Joseph and Ross, 2018). Kendeou and Van Den Broek (2007) argued that readers cannot be expected to understand the text if they lack the ability to link the new information with their prior knowledge.…”
Section: Elaboration: Extra-text Linkages With Prior Knowledgementioning
confidence: 99%
“…Given that dilemma, the only reasonable hope is that some jurisdictions and some cooperating researchers, teachers, designers, and developers will find ways to work in this direction, and that, as their efforts succeed in contrast with the status quo or other "reform" doctrines, their example may spread (O'Day & Smith, 2016). This of course is what all reformers hope, and hopes are often dashed.…”
Section: Concluding Thoughts For Policymakers With Implications For mentioning
confidence: 99%
“…Extending educational opportunity to those children in our society most in need, at greatest risk, is clearly a challenge that will require interventions not only in schools but also in a larger set of circumstances affecting children's lives. But when policy analysts and advocates assemble such broad-gauge strategies, teacher quality is invariably included in the mix (see for example, Duncan & Murnane, 2014;O'Day & Smith, 2016;Putnam, 2015;Rice, 2015).…”
Section: Introductionmentioning
confidence: 99%